Does Athletic Participation Signal Employability? An Experimental Analysis of Male and Female Athlete Job Applicants - Dwyer, Brendan; Gellock, Jennifer L (Journal of Intercollegiate Sport, 2018)
College athletes face high expectations to compete on the field and in the classroom. However, the time demands associated with athletics and academics often limit their ability to engage in traditional college experiences. Internships or practical job trainings are one such opportunity unfortunately forgone due to the time constraints of the contemporary college athlete experience. This results in an issue when applying for jobs outside of sport, as direct internship experience positively impacts an individual’s likelihood to be hired into an entry-level position. Through the application of signaling theory, the current study explored the perceived value of intercollegiate athletic participation compared to and in addition to direct internship experience via four résumé evaluation experiments. Two hundred and thirty five individuals with hiring experience participated; results suggested athletic participation was perceived as at least equally favorable to direct internship experience. However, male athletes without direct internship experience were more likely to receive an interview and received higher unobserved attribute ratings than female athletes with the exact same credentials.